Meniscal allograft transplants and new scaffolding techniques. Issue 6 (3rd June 2019) - Pereira, Hélder; Fatih Cengiz, Ibrahim; Gomes, Sérgio; Espregueira-Mendes, João; Ripoll, Pedro L.; Monllau, Joan C.; Reis, Rui L.; Oliveira, J. Miguel
Abstract : Clinical management of meniscal injuries has changed radically in recent years. We have moved from the model of systematic tissue removal (meniscectomy) to understanding the need to preserve the tissue. Based on the increased knowledge of the basic science of meniscal functions and their role in joint homeostasis, meniscus preservation and/or repair, whenever indicated and possible, are currently the guidelines for management. However, when repair is no longer possible or when facing the fact of the previous partial, subtotal or total loss of the meniscus, meniscus replacement has proved its clinical value. Nevertheless, meniscectomy remains amongst the most frequent orthopaedic procedures. Meniscus replacement is currently possible by means of meniscal allograft transplantation (MAT) which provides replacement of the whole meniscus with or without bone plugs/slots. Partial replacement has been achieved by means of meniscal scaffolds (mainly collagen or polyurethane-based). Despite the favourable clinical outcomes, it is still debatable whether MAT is capable of preventing progression to osteoarthritis. Moreover, current scaffolds have shown some fundamental limitations, such as the fact that the newly formed tissue may be different from the native fibrocartilage of the meniscus. Regenerative tissue engineering strategies have been used in an attempt to provide a new generation of meniscal implants, either for partial or total replacement. The goal is to provide biomaterials (acellular or cell-seeded constructs) which provide the biomechanical properties but also the biological features to replace the loss of native tissue. Moreover, these approaches include possibilities for patient-specific implants of correct size and shape, as well as advanced strategies combining cells, bioactive agents, hydrogels or gene therapy. Herein, the clinical evidence and tips concerning MAT, currently available meniscus scaffolds and future perspectives are discussed. Cite this article: EFORT Open Rev 2019;4 DOI: 10.1302/2058-5241.4.180103